Bioregulatory systems medicine: an innovative approach to integrating the science of molecular networks, inflammation, and systems biology with the patient's autoregulatory capacity? - Goldman, Alyssa W.; Burmeister, Yvonne; Cesnulevicius, Konstantin; Herbert, Martha; Kane, Mary; Lescheid, David; McCaffrey, Timothy; Schultz, Myron; Seilheimer, Bernd; Smit, Alta; St. Laurent, Georges; Berman, Brian (Frontiers in Physiology, 2015)
Bioregulatory systems medicine is a paradigm that aims to advance current medical practices. The basic scientific and clinical tenets of this approach embrace an interconnected picture of human health, supported largely by recent advances in systems biology and genomics, and focuses on the implications of multi-scale interconnectivity for improving therapeutic approaches to disease. This article introduces the formal incorporation of these scientific and clinical elements into a cohesive theoretical model of the bioregulatory systems medicine approach. The authors review this integrated body of knowledge and discuss how the emergent conceptual model offers the medical field a new avenue for extending the armamentarium of current treatment and healthcare, with the ultimate goal of improving population health.